Survey Pembelajaran Penjasorkes secara Daring di SMP/ Sederejat se-Kecamatan Donorojo Kabupaten Jepara - Oktamal, Dimas Sakti; Aji Putra, Ranu Baskora (Universitas Negeri Semarang, 2023)
Online learning is online learning, namely by conducting distance learning by utilizing online applications and internet networks. Online learning, especially in physical education learning, requires good readiness in terms of devices, teachers, and students who play a role in the success of physical education learning conducted online. The purpose of this study was to determine how readiness of learning tools, teacher readiness, and student readiness in carrying out physical and physical education online learning in SMP/equivalent in the Donorojo District, Jepara Regency in 2021. The results showed that the readiness of online learning tools in SMP/equivalent throughout the Donorojo District already meets the standards where the learning tools used have been adapted to online learning needs. Teachers' readiness in carrying out learning is reasonably good, and students' readiness is quite suitable, where it is vastly fulfilling in the form of student learning infrastructure to study online.